2022
DOI: 10.21608/ajas.2022.154162.1162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Spraying of Calcium and Boron Nano-fertilizers on Growth and Fruiting of Certain Pomegranate Cultivars

Abstract: Little is known about the effect of foliar nano-nutrients application on pomegranate trees. The experiment was split-plot arranged in a randomized complete block design on some pomegranate cultivars grown at the Experimental Orchard, Faculty of Agriculture, Assiut University, Egypt during three successive season of 2018, 2019 and 2020. The research was to study response of some pomegranate cultivars to foliar spraying with nano-boron and nano-calcium. All the tested applications significantly increased the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Too, such amending raised the TSS and vitamin C of juice around 7% and 26% comparing with control, respectively. These findings are of writing by these reported with Aseri et al (2008), Mosa et al (2014), El-Salhy et al (2015, Amin et al (2017) andEl-Salhy et al (2022). Who exposed that there is a beneficial effect of due using biological manuring for pomegranate trees production.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Too, such amending raised the TSS and vitamin C of juice around 7% and 26% comparing with control, respectively. These findings are of writing by these reported with Aseri et al (2008), Mosa et al (2014), El-Salhy et al (2015, Amin et al (2017) andEl-Salhy et al (2022). Who exposed that there is a beneficial effect of due using biological manuring for pomegranate trees production.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, it must be added in large quantities and repetitions that could be costly matter for farm practices and environmental pollution. Therefore, modern technologies which build on utilize biological manuring must be utilized for decreasing utilize of mineral nitrogen manures and their integrity of soil, animals, human and environment (Verma, 1990;Amin et al, 2017 andEl-Salhy et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those studies, a trial that evaluated apple production showed improvements in the amount of fruits from trees treated with nano-Ca 2 2% (Ranjbar and Ramezanian, 2020). Similarly, applications of calcium and boron resulted favorable in pomegranate fruits, promoting yield increase (El-Salhy et al, 2022).…”
Section: Results and Discussion Yield And Fruit Weightmentioning
confidence: 98%
“…The solutions were sprayed on the vegetative growth until the degree of complete wetness of the tree. Tween-20 dispersant was used at a concentration of 0.01% [14]. The spraying was carried out in the early morning.…”
Section: Methodsmentioning
confidence: 99%